Optimization of energy storages in microgrid for power generation uncertainties - Ali, Loaqat (Curtin University, 2016)
Microgrid is a cluster of distributed generation units, energy storages, and loads which can operate grid-connected and islanded. This research focuses on selecting an economic standalone supply system for small and remote off-grid towns in Western Australia. Existing power systems of such towns have adverse environmental impacts due to the utilization of diesel and gas. The suitable electricity supply system is a hybrid system composed of generators, renewables, and energy storages.